The Protective Effects of Apigenin on Cognitive Function and The Brain Transcriptome in Old Mice. (17th December 2021) - Cavalier, Alyssa; Clayton, Zachary; Hutton, David; McEntee, Cali; Seals, Douglas; LaRocca, Thomas
Abstract: Age-related declines in cognitive function increase the risk of developing mild cognitive impairment and dementia, but select nutraceuticals (bioactive plant compounds) may hold promise for protecting the brain and improving cognitive function with age. Apigenin is a flavonoid nutraceutical found in chamomile and reported to inhibit multiple hallmarks of aging; however, it has not been studied in the context of brain aging specifically. We treated young (6 mo) and old (27 mo) C57BL/6N mice with apigenin (0.5 mg/mL in 0.2% carboxymethylcellulose) or control (0.2% carboxymethylcellulose) drinking water for 6 weeks. Then, we assessed cognitive function and performed RNA-seq to characterize global transcriptomic changes and potential mechanisms of action in the brain. We observed impaired novel object recognition (NOR) test performance (an index of learning/memory) in old vs. young control mice (P<0.0001), but old apigenin mice had 3-fold higher NOR performance relative to old control mice (P=0.02). Transcriptomic analyses also showed age-associated gene expression changes related to immune function and inflammation, consistent with the established role of inflammation in brain aging. However, some of these key changes were reversed by apigenin. In fact, >300 genes were differentially expressed in old apigenin-treated mice vs. old controls, and the biological processes linked with these differences were related to innate and adaptive immune function, and cytokine and chemokine regulation. We are performing protein/signaling pathway analyses to elucidate downstream cellular changes associated with apigenin treatment, but our current results suggest apigenin may be a promising nutraceutical candidate for preventing brain aging.